Chemo-resistant gestational trophoblastic neoplasia: a review of cases at a tertiary cancer centre - R. Mirji, Sharayu; M. Patel, Shilpa; S. Arora, Ruchi; D. Desai, Ava; H. Mankad, Meeta; K., Sangeetha; P. Panchal, Harsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational trophoblastic neoplasia (GTN) was earlier a dreaded malignancy with high mortality rates. GTN is now considered to be one of the most curable solid tumours in women with cure rates greater than 90% even in the presence of metastases. Despite the high chemo sensitivity, treatment failure or drug resistance has been described in both groups. Methods: In this study, available records of GTN cases over 6 years were reviewed with emphasis on those who were resistant to the first line of chemotherapy. Of these, 37(34.58%) were resistant to the first line of chemotherapy. These cases were studied with respect to age, parity, antecedent pregnancy, interval from antecedent pregnancy, pretreatment β hCG, risk score and presence of metastases. The data was analyzed in order to find any risk factors associated with chemo-resistance. Results: Total number of cases of GTN was 107. Out of these 107 cases, 63 (58.88%) were low risk and 44 (41.12%) were high risk according to FIGO scoring system. Complete response was achieved with first line chemotherapy in 70 (65.42%) patients. The remaining 37 (34.57%) were resistant to first line chemotherapy. In the low risk group, 30 (47.62%) cases, and in the high-risk group, 7(15.91%) were resistant to first line of chemotherapy. Conclusions: Despite the high chemo sensitivity of GTN, resistance to first line chemotherapy may be encountered in up to 40% of cases. It is important to identify the patients who are at risk to develop resistance, early identification of resistance and change of chemotherapy so as to minimize the exposure of these patients to ineffective chemotherapy.